Efektifitas Pemberian Posisi Alih Baring Terhadap Kejadian Dekubitus Pada Pasien Stroke - Donny Richard Mataputun; Jihan Apriani (NHM PRESS, 2023)
Introduction: Decubitus ulcer is a wound area that is exposed to pressure in the area of ​​​​the skin covering the bone that looks protruding out or in contact with medical equipment, pressure sores will occur if the skin continuously rubs together for a long time, the incidence of pressure sores can be overcome by being given a change in position in accordance with abilities such as changes in activities and routine activities by giving bed-shift actions every 2 hours and 4 hours. Many efforts have been made to help reduce the incidence of pressure sores, one of which is bed transfer. Purpose: To analyze the effectiveness of the recumbent position on the incidence of pressure sores in stroke patients from previous researchers. Design: Literature Review, Data Source: Search using Google Scholar database, articles on topics published in Indonesian and English from 2016-2022. Review Method: Search articles using PICOTS with keywords that match the writing. Articles are selected by journal selection, abstract selection with inclusion and exclusion criteria so as to find journals that can be reviewed. Results: Literature review of 7 selected articles. Consists of journals (Novitasari, E., Yuswatiningsih, E., Ningrum, 2018) (Lubis & Saraswati, 2018) (Kusumah, A.M.P., Hasibuan, 2021) (Mayangsari, 2020) (Faridah, 2019) (Choi et al., 2021) (Hassan, 2020). These characteristics indicate the importance of changing positions for stroke patients. Conclusion: overall there are differences in characteristics in the journals showing that all of them use position changes to reduce pressure sores. Suggestion: it is hoped that further researchers will study more sources and references related to Bed Shift so that the results of the journal literature review research are even better.